Studies on the post-ictal rise in seizure threshold. - Nutt, D; Cowen, P; Green, A (1981)
Seizure thresholds were determined by timed infusion of a convulsant drug. Following an electroconvulsive shock (ECS) rats exhibited a raised seizure threshold to infusion of the GABA antagonist drugs, pentylenetetrazol, bicuculline and isopropyl-bicyclophosphate, but not to the glycine antagonist strychnine or the 5-HT agonist, quipazine. The increase in threshold was seen following a bicuculline-induced seizure and 30 min following the last of a course of ECS given once daily for 10 days. The rise in seizure threshold still occurred when animals were pretreated with alpha-methyl-p-tyrosine (200 mg . kg-1), p-chlorophenylalanine (200 mg . kg-2), naloxone (1 mg . kg-1) or indomethacin (20 mg . kg-1). Diazepam (2 mg . kg-1), flurazepam (10 mg . kg-1) and sodium valproate (400 mg . kg-1) elevated basal seizure threshold and a further rise followed the ECS. Phenytoin (40 mg . kg-1) and carbamazepine (40 mg . kg-1) had no effect on basal seizure threshold or the ECS-induce rise. (¿Propranolol (20 mg . kg-1) did not affect basal seizure threshold but prevented the ECS-induced increase. The rise in seizure threshold following a convulsion may be an important adaptive mechanism which could be related to the reported increase in specific benzodiazepine binding following a seizure.